Efectos de la infraestructura pública sobre el crecimiento de la economía, evidencia para Chile - Rivera, Jorge; Toledo, Patricia (Estudios de Economía, 2016)
In contrast to other empirical studies, this paper analyzes the effect of publicinvestment on infrastructure on the Chilean growth. Based on Glomm andRavikumar (1994) and Yoke (2001), we present a stochastic model to test thehypothesis of endogenous growth against exogenous growth. On the basis ofthis model we estimate a long-run relationship among output, public investmentin infrastructure and private capital. This relationship is verified usingthe Johansen’s cointegration test during the 1975-2000 period. The results showthat there is a positive relationship between output and public investment ininfrastructure. However, this outcome is neither consistent with the exogenousgrowth hypothesis nor public investment spillovers. In spite of that, the estimatessuggest that an increase of 10% in public investment in infrastructure generates an increase of 1.6% in total output (both variables expressed in perworkers terms).